Metabolic and haematological responses of Labeo rohita to dietary fucoidan. Issue 1 (1st January 2018) - Gora, Adnan Hussain; Sahu, Narottam Prasad; Sahoo, Sujata; Rehman, Saima; Ahmad, Irshad; Agarwal, Deepak; Dar, Showkat Ahmad; Rasool, Sheikh Irfan
ABSTRACT: Immunomodulatory properties of fucoidan have been extensively studied in fish. However the effect of dietary fucoidan on the metabolic enzymes is not studied in detail with respect to aquatic organisms. An investigation of the effect of dietary fucoidan on the metabolic and haematological status of Labeo rohita fingerlings is presented. One hundred and eighty fingerlings were distributed into four experimental groups in triplicates. Each group was fed isonitrogenous and isoenergetic diets containing 0% fucoidan (T1), 1% fucoidan (T2), 2% fucoidan (T3) and 3% (T4) seaweed powder to satiation for a period of sixty days. Dietary fucoidan was found to significantly ( P < 0.05) reduce malate dehydrogenase and aspartate aminotransferase activity in the liver tissue. Alanine aminotransferase activity in the muscle tissue of fucoidan fed groups was significantly higher than the control. The liver and gill superoxide dismutase activity was significantly reduced in the fucoidan fed groups compared to the control. The catalase activity in the liver and gill was significantly lowered in the T3 group. The blood profile of the different experimental groups also revealed beneficial effects of dietary fucoidan yielding a superior haematological status in the groups fed with fucoidan.